Expanding education opportunities in protracted emergencies: A case of two schools in one in Kakuma refugee camp - Sandra Akello; Marangu Njogu; Darius Isaboke (University of Bath, Centre for Development Studies (CDS), 2020)
The purpose of this article is to develop a comprehensive understanding of the innovation of the Two Schools in One effectiveness in expanding secondary education opportunities in refugees' settings. The study was conducted between October 2017 and May 2018 in Kakuma of Kenya. The researchers used qualitative methodologies to collect data from the teachers, students, parents and NGO representatives from UNHCR and LWF. A total of 38 respondents participated in the interview. Purposeful sampling was used to identify respondents even though the study was not aimed at achieving statistical representation of the population. The results highlight that the theory of change is explicit in 'Two Schools in One'. Students were able to access quality education by sharing resources. This addressed issues of limited learning spaces, thus, it provided education for students and supported their transition from primary to secondary education in protracted situations. The increased demand for quality education for refugees will be met with an increased supply of teachers, more relevant learning materials and more classrooms for girls and boys. This supply and demand relationship will become self-reinforcing as more innovative approaches are considered to address the supply and demand side factors and to tackle both material challenges and knowledge/ attitudes/ practices in order to provide education to as many students as possible.
Keywords: 330; Protracted emergencies; Secondary school; Kakuma refugee camp; Education and NGO